Synthesis of Molecularly Imprinted Polymer for the Removal of Melamine - Rachel Marcella, Roland; Showkat Ahmad, Bhawani (Asian Journal of Chemistry, 2019)
In this article, molecularly imprinted polymer (MIP) of melamine was synthesized by non-covalent approach using microemulsion medium. In this study, melamine is used as a template molecule, acrylic acid as a functional monomer, N,N′-methylenebis(acrylamide) (MBAm) as a cross-linker and 2,2′-azobisisobutyronitrile (AIBN) as an initiator and microemulsion as a solvent. The produced polymers were characterized by Fourier transform infrared spectroscopy (FT-IR), transmission electron microscopy (TEM), Brunauer-Emmett-Teller (BET) and thermogravimetric analysis (TGA). The batch binding analysis was conducted for the evaluation of MIP and NIP rebinding efficiency with the melamine template. The adsorption studies including the adsorbent dosage of polymer, initial concentrations and pH of melamine solution were successfully carried out on both MIP and NIP. For selectivity test, 2,4,6-trichlorophenol was chosen as the competitive molecule against melamine template. A very good relative selectivity coefficient was achieved. The removal of melamine from different samples were conducted successfully by achieving a good removal efficiency in milk, river water and human blood serum 84.30, 94.26 and 93.32 %, respectively.